Extent of Spending Leisure Time through the Electronic Media and Drug Behaviour of Youth - Rojková, Zuzana; Mydlová, Kristína (Communication Today, 2025)
The study deals with the issue of the influence of mass media on the behaviour of youth. Specifically, it is about the extent of leisure time spent using electronic media in relation to drug behaviour (alcohol consumption, cigarettes, marijuana, illicit drug use). It is an exploratory, correlational, non-experimental research. The sample consisted of 2,133 elementary and secondary school pupils (39.6% of them were boys and 60.4% girls). The data was obtained through the SAHA questionnaire (i.e. The International Social and Health Assessment, originally proposed by Weissberg et al. in 1991). Relations were examined in two age groups – “14” (≤ 15 years, n = 743) and “16” (≥ 16 years, n = 1,390). The results show a weak, but statistically significant correlation between time spent with electronic media, especially on the Internet and all forms of drug behaviour except illegal drug use, to a larger extent in the older age group.